Landscape of Stress Response and Virulence Genes Among Listeria monocytogenes Strains - Lakicevic, Brankica Z.; Den Besten, Heidy M. W.; De Biase, Daniela (Frontiers in Microbiology, 2022)
The pathogenic microorganism Listeria monocytogenes is ubiquitous and responsible for listeriosis, a disease with high mortality rate in susceptible people. It can persist in different habitats, including the farm environment, the food production environments, and in foods. This pathogen can grow under challenging condition, such as low pH, low temperatures and high salt concentrations. However, L. monocytogenes has a high degree of strain divergence regarding virulence potential, environmental adaption and stress response. This review seeks to provide the reader with an up to date overview into clonal and serotype-specific differences among L. monocytogenes strains. Emphasis on the genes and genomic islands responsible for virulence and resistance to environmental stresses is given to explain the complex adaptation among L. monocytogenes strains. Moreover, we highlight the use of advanced diagnostic technologies, such as whole genome sequencing, to finetune quantitative microbiological risk assessment for a better control of listeriosis.